Tandem ssDNA in neutrophil extracellular traps binds thrombin and regulates immunothrombosis - Weijie Guo; Sihao Huang; Xiangli Shao; Yuting Wu; Yuan Ma; Shuya Lu; Hanlin Ren; Xuening Zhou; Zhenglin Yang; Mingkuan Lyu; Yiwei Liu; Vernita Gordon; et al. (Proceedings of the National Academy of Sciences, 2025)
Neutrophils release neutrophil extracellular traps (NETs) to neutralize infections, a process that also contributes to immunothrombosis. While beneficial in localized infections, excessive NET formation can lead to widespread coagulopathy and organ failure. While the roles of NET-associated proteins such as histones in immunothrombosis are well characterized, NET-derived DNAs are much less known. To address this issue, we report herein the direct interaction between thrombin and DNA scaffolds and further, the identification of short tandem repeats of single-stranded (ATTCC) n in NETs that selectively bind thrombin, a crucial enzyme involved in both blood clot formation and immune response. We have also developed a strategy of selective targeting ss(ATTCC) n using antisense locked nucleic acids (LNAs), effectively disrupting NET–thrombin interactions. This finding reveals an unexplored role of single strand DNA (ssDNA) within NETs and provides a broad avenue for developing targeted therapeutic interventions for immunothrombosis-related disorders.